Optimization of nano-silica in enhancing the properties of synthetic based drilling fluids for tight gas reservoir conditions - Ndubi, Mathews; Ben Mahmud, Hisham (IOP Publishing, 2019)
The nano-silica in drilling fluids is commonly used to improve the performance of drilling fluids, mainly water and oil based muds. Tight gas reservoirs are experienced a myriad of problems during drilling. One of the problems is the gas influx into the wellbore because of the abnormal pore pressure, fluid loss due to the fracture pressure and pore pressure is very narrow margin, stuck down hole equipment in the wellbore due to high differential pressure between hydrostatic pressure and pore pressure. Another problem is related to drilling mud and cement. However, not much studies have been done on the effect of nano-silica in invertemulsion drilling fluids. This research paper focuses on how nano-silica influences the performance of invert-emulsion/synthetic based mud in tight gas reservoirs at harsh operation conditions, high pressure high temperature (HPHT). Synthetic based mud has been selected as an ideal drilling fluid to be used in HPHT tight gas reservoirs due to its superior qualities. In order to objectify this study, numerous experiments sets have been carried out in which different concentrations of nano-silica with respect to the fluid loss agent have been added to the synthetic based mud and the resultant performance is carefully studied in order to determine the optimum concentration of nano-silica that will elicit the best performance from synthetic based drilling fluids. The obtained results showed that a maximum concentration of about 40% provides the best performance Nano-silica has also improved the rheological properties of SBM by reducing the plastic viscosity and yield points.